2021
DOI: 10.1111/1468-0009.12522
|View full text |Cite
|
Sign up to set email alerts
|

Population Health Innovations and Payment to Address Social Needs Among Patients and Communities With Diabetes

Abstract: r Population health efforts to improve diabetes care and outcomes should identify social needs, support social needs referrals and coordination, and partner health care organizations with community social service agencies and resources.Context: Increasingly, health care organizations are implementing interventions to improve outcomes for patients with complex health and social needs, including diabetes, through cross-sector partnerships with nonmedical organizations. However, fee-for-service and many value-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…40 Future research evaluating the integration of SDoH strategies should incorporate longer time horizons to fully understand the health benefits of these approaches. 41 This study has several limitations. The close connection of the clinics within the same health system was a limiting factor in that some control sites began adopting elements of the DCII during the study period, thus reducing our ability to capture the full impact of the DCII.…”
Section: Discussionmentioning
confidence: 92%
“…40 Future research evaluating the integration of SDoH strategies should incorporate longer time horizons to fully understand the health benefits of these approaches. 41 This study has several limitations. The close connection of the clinics within the same health system was a limiting factor in that some control sites began adopting elements of the DCII during the study period, thus reducing our ability to capture the full impact of the DCII.…”
Section: Discussionmentioning
confidence: 92%
“…Our simplified SDoH clusters could also be used to inform risk adjustment for more appropriate payment for organizations serving higher-risk patient populations. 33,34 Our study builds on prior literature linking SDOH to adverse chronic disease outcomes. A study using the National Health and Nutrition Examination Survey found that race (black vs white) and insurance status (uninsured vs insured) were strongly associated with uncontrolled hypertension among US adults with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Many insurance plans provide limited or no coverage for interventions to address patients' social needs and SDOH. 32 Interventions for marginalized populations are frequently held to the higher bar of cost savings rather than value. For example, the Affordable Care Act of 2010 required budget neutrality or cost savings for models of the Center for Medicare and Medicaid Innovation (CMMI) to be continued even if there were big payoffs in health with slightly more money included.…”
Section: Implementing Antiracist Payment Reformmentioning
confidence: 99%